Website Destinasi Wisata Di Kabupaten Karanganyar dengan Wordpress - Devi Rizki Zahrahwani (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Politeknik Pratama Mulia Surakarta, 2020)
Tourism websites in Karanganyar Regency are used as a tool to deliver information and new tourism promotion media in Karanganyar Regency to people who want to know new and populer toursin Karanganyar Regency. The website is one form of regional tourism promotion in Karanganyar Regency, in order to attract tourist to visit the Karanganyar Regency. This website is useful as an information and as a place for tourism promotion in Karanganyar Regency. Themore tourist visiting, the income of surrounding community and regional income will increase. Methods of research carried out direct observation, interview with the government and through mass media related to the issue raised. Touris website in Karanganyar Regency are made using WordPress and with MySQL database and the time of research began in April 2019.